Relationship between atopic manifestations, family history of atopic disease and cord blood IgE levels in children - Tisnasari Hafsah; Myrna Soepriadi; Budi Setiabudiawan; Herry Garna (Paediatrica Indonesiana, 2007)
Background The incidence of atopic disease tends to increaseover the past few decades and its morbidity interferes with thequality of life and health. Prediction of the disease is importantfor early prevention.Objective To evaluate the relationship between atopicmanifestations, family history (FH) of atopic disease and cordblood IgE (CB-IgE) levels.Methods We conducted an analytic observational study withcohort retrospective design on children with an average age of 3years whose CB-IgE had been measured at delivery inKiaracondong Primary Health Care during October–December2004. Manifestations of atopic disease were recorded using ISAACquestionaire for allergy. Chi-square, Mann-Whitney test, andlogistic regression analysis were used for analysis.Results Cord blood IgE was measured on 124 children after birth.Only 94 children (76%) fulfilled the inclusion criteria. Atopicdisease was found in 17 children (18%), consisting of 8 childrenwith atopic dermatitis, 4 with allergic rhinitis, and 5 suffered fromboth. There were significant differences in the mean value of CB-IgE (Z M-W =4.60; P<0.001) and FH (x 2 =19.059; P<0.001)between atopic and non atopic children. Cut off point of the CB-IgE concentration was 1.4 IU/mL (77.7%). The highest probabilityfor atopic manifestations was found in children who had highCB-IgE and positive FH (P=45%). Relative risk of children withhigh CB-IgE level in positive FH group was 3.636 (95% CI0.943;14.016).Conclusion CB-IgE level and family history of atopic disease arerisk factors for the development of atopic manifestation.